2011
DOI: 10.2174/1876524601104010045
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Nephropathy in Spontaneously Diabetic Torii (SDT) Rats

Abstract: Diabetic nephropathy is a serious complication of diabetes mellitus, making it essential to develop animal models of diabetic complications to simulate the pathogenesis in humans. We monitored pathobiochemical parameters and histopathological findings of kidneys in male Spontaneously Diabetic Torii (SDT) rats. Renal-related parameters in SDT rats have deteriorated with the progress of diabetes mellitus, and histopathological changes in the renal tubules and the glomeruli were observed with aging. Glycemic cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…On the other hand, the renal tubular lesions markedly increased with age, with a severe increase in tubular glycogen deposition at 50 and 68 weeks (Figure 6(h)). In addition, urine volume, urine protein, and urine albumin increased with blood glucose at 24 weeks and thereafter, and these changes may be consistent with the development and progression of renal lesions [41, 42]. These renal lesions were also improved by blood glucose control with insulin and thus shown to result from the exposure to high blood glucose [41, 42].…”
Section: Complicationsmentioning
confidence: 95%
“…On the other hand, the renal tubular lesions markedly increased with age, with a severe increase in tubular glycogen deposition at 50 and 68 weeks (Figure 6(h)). In addition, urine volume, urine protein, and urine albumin increased with blood glucose at 24 weeks and thereafter, and these changes may be consistent with the development and progression of renal lesions [41, 42]. These renal lesions were also improved by blood glucose control with insulin and thus shown to result from the exposure to high blood glucose [41, 42].…”
Section: Complicationsmentioning
confidence: 95%
“…It has been reported that the male SDT rats develop diabetes from about 20 weeks of age and that renal lesions accompanied by increases in urine volume and renal function parameters (urinary protein and urinary albumin) are observed from about 24 weeks old (Sasase et al, 2013). The renal lesions and alteration of the renal function parameters observed in the SDT rats are enhanced with the progress of diabetes and the renal lesions are improved by blood glucose control with insulin (Ohta and Sasase, 2011;Ohta et al, 2007). Therefore, the renal lesions observed in the SDT rats are considered to result from exposure to high blood glucose.…”
Section: Introductionmentioning
confidence: 99%